Real Anomalies - van BINSBERGEN, JULES H.; OPP, CHRISTIAN C. (Journal of Finance, 2019)
ABSTRACT We examine the importance of cross‐sectional asset pricing anomalies (alphas) for the real economy. To this end, we develop a novel quantitative model of the cross‐section of firms that features lumpy investment and informational inefficiencies, while yielding distributions in closed form. Our findings indicate that anomalies can cause material real inefficiencies, which raises the possibility that agents who help eliminate them add significant value to the economy. The model shows that the magnitude of alphas alone is a poor indicator of real outcomes, and highlights the importance of the alpha persistence, the amount of mispriced capital, and the Tobin's q of firms affected.